PEMBUATAN BIOGAS DARI LIMBAH TERNAK SAPI PERAH DAN PUPUK ORGANIK AMPAS BIOGAS KERING - Novariyanto, Rizki Agung; Setiawan, Hendri (JPM Pambudi, 2017)
Kemiri is a village in Malang located on the border of the District Malang with Pasuruan region. Most of the people are farmers lading and maintain dairy cows as their daily work. Impurities cause waste that pollute the environment in the form of odor and contaminate soil and water. Cow dung Colly contains toxins and bacteria that endanger human health and the environment. The results of the survey team IbM and analysis of problem situations faced by Partner IbM, very urgent and need help are as follows: (1) Waste cow manure Partners cause environmental pollution, (2) Lack of energy for cooking are still using firewood and LPG subsidy (3 Kg) that it is still heavy, (3) Not understanding Biogas manufacturing technology and lack of capital. (4) Expensive and scarce chemical fertilizer in the field, (5) the limitations of materials and equipment manufacture organic fertilizer. On the basis of the measures to solve the problem is (1) Holding Extension of cleanliness, making biogas and organic fertilizer packaging of the pulp biogas (bioslurry), (2) Preparation of tank biogas (digester) type Fixed Dome made of brick or concrete, and their installations and equipment up to the utilization / operations, (3) dry Organic Fertilizer Production packaging 25 Kg of bioslurry. Thus, the target output or outcome in Service program is the biogas as a source of energy / fuel for IBM partners fund and organic fertilizer packaging 25 Kg as a substitute for chemical fertilizers and unnatural.